Religious Indoctrination in The 2013 Islamic Religious Education Curriculum: A Content Analysis Of Teaching Materials And Its Implications - Ifah Khadijah; Hoerul Umam (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study conducts a comprehensive analysis of the 2013 Islamic Religious Education curriculum, using the framework of religious indoctrination theory. It examines the curriculum's impact on learners, particularly its potential to restrict creativity or promote independent thinking. The study investigates the curriculum and related materials, employing qualitative content analysis to uncover embedded meanings. Findings reveal the curriculum's susceptibility to indoctrination, particularly when hindering students' critical thinking. The analysis highlights several key observations: (1) The 2013 curriculum prioritizes memorization over comprehensive understanding; (2) Textbooks and teacher's books encourage passive acceptance of Islamic teachings, lacking critical thinking promotion; and (3) Teacher's books lack specificity, allowing individual religious orientations to influence instruction, potentially perpetuating negative practices.